1993
DOI: 10.1038/bjc.1993.299
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical detection of P-glycoprotein and GSTP1-1 in testis cancer

Abstract: Summary P-glycoprotein (Pgp) and pi-class glutathione S-transferase (GSTPI-1) are thought to be correlated with multiple drug resistance. In immunohistochemical staining, non-seminomatous germ cell tumours, which are more refractory than seminomas to anti-cancer chemotherapy, frequently expressed Pgp and GSTP1-1. Western blot analysis demonstrated lower amount of GSTPl-l in seminoma than in teratoma. These results suggest that Pgp and GSTPI-I might contribute to drug resistance in testis cancers

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 21 publications
1
15
1
1
Order By: Relevance
“…Pgp expression was observed in 27% of tumours, in agreement with previous reports (35%, Katagiri et al, 1993;33%, Eid et al, 1998). In contrast to the report by Eid et al (1998), we found no association between Pgp expression and nonseminomatous histology or advanced stages of disease.…”
Section: Discussionsupporting
confidence: 82%
“…Pgp expression was observed in 27% of tumours, in agreement with previous reports (35%, Katagiri et al, 1993;33%, Eid et al, 1998). In contrast to the report by Eid et al (1998), we found no association between Pgp expression and nonseminomatous histology or advanced stages of disease.…”
Section: Discussionsupporting
confidence: 82%
“…Wc have recently shown that MAb C494 crossreacts with pyruvate carboxylase (PC), and a search for epitopespecific sequences of MAb C494 revealed that mouse PC contains four of the five most reactive amino acids (REG) near the carboxy terminus (17). Although the epitope of MAb JSB-1 has not been characterized, it is being widely used for immunohistochemical detection of P-gp in clinical tissues specimens (18,19). We show here that the MAb JSB-1 also crossreacts with PC under both immunoblotting and immunohistochemical conditions.…”
Section: Introductionmentioning
confidence: 73%
“…In summary, MAb JSB-1 is known for excellent immunostaining of P-gp in formalin-fixed, paraffin-embedded, and frozen tissue sections (34), and is widely used for detection of MDRl P-gp expression in clinical specimens (18,19,35). The present study shows intense immunohistochemical staining with MAb JSB-1 in a tissue lacking expression of MDRl P-gp and has identified at least one crossreactive polypeptide as PC, an enzyme abundant in mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…The high expression of GST-pi in many neoplasms was related to the resistance of anticancer drugs. Katagiri et al reported that the expression of GST-pi negatively correlated to the sens etivity of anticancer drug in testicular tumor [6] . Dong J suggested that the expression of GST-pi closely related to resistance of anticancer drug in ovariogenic neoplasm [7] .…”
Section: Biological Characters Of Gst-pimentioning
confidence: 99%